DIPG-77. INTRATUMORAL PHARMACOKINETICS OF CHEMOTHERAPY IN DIPG: XENOGRAFT AND INITIAL PHASE 0 CLINICAL TRIAL RESULTS. Issue 2 (22nd June 2018) - Green, Adam; Flannery, Patrick; Hankinson, Todd; O'Neill, Brent; DeSisto, John; Lemma, Rakeb; Hoffman, Lindsey; Levy, Jean Mulcahy; Raybin, Jennifer; Hemenway, Molly; Koschmann, Carl; Handler, Michael; et al.
Abstract: INTRODUCTION: Hundreds of chemotherapy trials have been conducted in diffuse intrinsic pontine glioma (DIPG) without survival improvement. One potential reason is a lack of intratumoral penetration, but this has not previously been assessed in humans. We used gemcitabine as a model agent to assess DIPG intratumoral pharmacokinetics (PK). We chose gemcitabine for its known blood-brain barrier penetration and established pediatric safety data. METHODS: We first assessed intratumoral PK in a mouse orthotopic xenograft model of DIPG. We subsequently opened a phase 0 trial in which newly-diagnosed DIPG patients receive one intravenous gemcitabine dose immediately before biopsy. We measured gemcitabine concentration by liquid chromatography-tandem mass spectrometry. RESULTS: In the xenograft model, intraperitoneal gemcitabine showed a significantly greater tumor/normal brain penetration ratio in cortical compared to pontine tumors (p=0.032). Based on these results, we began our phase 0 trial. In the first patient enrolled, concentrations from four spatially heterogeneous tumor biopsies ranged from 4.8–9.7 µM. These compare favorably to intratumoral gemcitabine levels published from a similar study in adult glioblastoma (0.06–3.6 µM) and to our measured in vitro IC50 levels in three DIPG cell lines (44–162 nM). Levels were similar to those found in our xenograft pontine tumors (3.4–7.3 µM, p=0.24). CONCLUSIONS/CURRENT WORK: We demonstrated adequate intratumoral chemotherapy penetration for therapeutic effect in DIPG, suggesting that this is not the reason for chemotherapy failure. We are now analyzing samples from a second trial subject, and from a xenograft study comparing penetration and clearance rate based on H3K27M mutant/wild-type status and tumor location.